The Effect of Metacognitive based Learning Process on Environmental Pollution Subject towards Students’ Cognitive Competence - Aditya Rahman; Dwi Ratnasari; Silvy Destianingsih; Nurul Rahmah Kusumaputri (Bioeducation Journal, 2020)
This research aims to determine the effect of metacognitive-based biology learning process towardsstudents’ cognitive competenceon environmental Pollution subject of class X SMA Plus Putra Bangsa Tangerang District. The method used in this research was quasi-experimental method. The population was all class X MIA with X MIA 1 of 17 people as the control sample and X MIA 2 of 18 people as the experimental sample. The instrument in this research were a test of students’ cognitive competence, a metacognitive competence questionnaire, and a compliance sheet. Based on the results of the research it can be concluded that there were differences in cognitive competence of students between the experimental class that was treated using a metacognitive basis and the control class that was treated using a conventional basis on environmental Pollution subject. The average score of cognitive competence in the control class was 53.09 which was included in the “sufficient cognitive” category. The result showedthe score of 68.61, which was included in the “goodcognitive” category. In the hypothesis test, it can be concluded that there was an impact of the use of Metacognitive-based learning process on students’ cognitive competence on environmental pollution subject.